Palliative care in heart failure – results from systematic audits in an acute trust. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Hookey, Claire; Satchithananda, Duwarakan; Anderson, Susan; Barker, Philomena; Howells, Alison; Moss, Amanda
Abstract : Background: The 2009 European Society of Cardiology Position statement on Palliative Care in Heart Failure concluded that palliative care should be considered part of comprehensive care provision over the whole disease trajectory. The statement was produced by specialists, but most heart failure (HF) care is delivered by generalists. It is unclear to what extent generalists engage with palliative care in HF. Aim: To audit physicians' understanding of palliative care needs and engagement with palliative care services in HF. Methods: Three audits of inpatient HF care were undertaken: acute care (n=80 inpatients), referrals to specialist HF nurses (n=50 inpatients), and HF knowledge in general physicians (n=23 physicians). Results: (1)Only 6% of patients discharged were assessed by physicians to be in palliative (symptomatic treatment only) or end stage (life expectancy 6-12 months) HF. However 40% died within 6 months. (2) Physicians only occasionally consider palliative or terminal care needs of inpatients with HF. (3) Physicians rarely ask for palliative or terminal care advice from specialist HF nurses or palliative care services. Conclusion: Physicians responsible for the care of HF patients overestimate patients' prognosis. This may explain their reluctance to consider the palliative or terminal care needs of patients or to seek advice from palliative care or HF specialists. Failure to identify that patients are approaching end of life will result in inadequate discussion with patients regarding end of life issues and an absence of advance care planning. In order to implement best practice in palliative care for heart failure it will be necessary to engage general physicians and address their training needs.